Nepasirodę knygotyros leidiniai - Žukas, Vladas (Knygotyra, 1991)
In 1941 an attempt to publish an annual on book history “Bibliotheca Lituana” was disrupted by the war. The Director of the State Library in Kaunas J. Rimantas attempted to publish the annual during the war. In June, 1944 a collection of articles and illustrations (about 400 pages) was prepared but wasn’t put to press. The topics of the collection varied – general book history, the history of Lithuanian literature and printing, art of books, circulation, history of libraries, library activities and some issues on the history of culture. The most outstanding research was done by V. Biržiška (“Unknown Early Lithuanian Works and Writers”) and K. Avižonis (“The XVII Century Radzvill Library in Nesvyžius”). The collection, however, failed to come out after the war.In 1947 a new attempt was made by J. Rimantas – “The Library Annual” – was prepared. The subject matter of the annual deals with the organization of libraries in Lithuania, bibliography, history of print.The preparation of “Bibliotheca Lituana” and “The Annual of Libraries” proves an increased interest of Lithuanian scientists in book history, attempts to publish research regularly.